First epidemiological description of tegumentar and visceral Leishmaniasis in Patrocínio Municipality, Minas Gerais (2000-2017) (Bioscience Journal, 2020)
Leishmaniasis is a disease that can affect visceral organs (visceral leishmaniasis; VL) or mucous membranes and skin, causing lesions of different forms and levels of severities (tegumentary leishmaniasis; TL). Like several others, leishmaniasis is a neglected disease, as the pharmaceutical industry seems to show little to no interest in developing new drugs targeting the disease. This study aims to trace the epidemiological profile of leishmaniasis in the Municipality of Patrocínio, State of Minas Gerais, over a period of time. Secondary data of reported cases from 2000 to 2017 were analyzed as provided by the Patrocinio Health Department. As no literature was found on the status of such a disease in Patrocinio, it is important to trace the epidemiological profile of leishmaniasis in the area. The findings pointed out that the disease affected predominantly male in the economically active population, mainly from the urban area, and that it had no relationship with professional activity. Twenty-two cases of leishmaniasis (15 of TL and 7 of VL) were reported, all of which were treated and cured. Five cases of TL and 1 case of VL were autochthonous, and confirmed cases of canine infection took place in 2011, 2016 and 2017.